Rancang Bangun Alat Pencacah Sampah Organik Pekan Ternak Sapi - Emon Azriadi; Muhammad Tarmizi; Aris Fiatno; Yesi yusmita; Resy Kumala Sari (Research Center University of Pahlawan Tuanku Tambusai, 2020)
Abstract Garbage is something that disturbs and affects the community environment. Organic waste comes from living things, both humans, animals, and plants, so that it can be used for animal feed which is processed by chopping. As for the results of field observations at the Bangkinang Kota market, it can be seen that organic waste types of cabbage and mustard are commonly found in the Bangkinang Kota market, organic waste such as carrots, tomatoes, chilies, potatoes and kale are found in many trash cans but the amount is less, this type of waste dry. For the Bangkinang City area, waste transportation is carried out 2 (two) times a day, namely in the morning and evening. The most waste generated is on Wednesdays and Sundays, because those days are market days in Bangkinang Kota. The waste generated reaches 1-2 tons per day. The organic waste chopper generally consists of a frame, top casing, bottom casing, inlet, outlet, axle, bearing, and blade. The manufacture of this tool at the Laboratory of Industrial Engineering, Universitas Pahlawan Tuanku Tambusai. The design and manufacture of organic cattle feed chopper has a size of 38 cm, width 51 cm and height 120 cm, using a 7 hp/5600 rpm diesel engine with a weight of 72 kg. Based on the test results, it can be concluded that organic mixed vegetable waste weighing 2 kg only takes 22 seconds faster, while cabbage weighing 2 kg takes 37 seconds and mustard greens weighing 2 kg takes 29 seconds. The amount of organic waste that is chopped as much as 6 kg only takes 88 seconds. Keywords: Design, chopper, organic waste.